A Modular Three-Dimensional Scenario-Based Numerical Modelling of Groundwater Flow - Omar P.J.; Gaur S.; Dwivedi S.B.; Dikshit P.K.S. (My University, 2025)
Groundwater flow modelling is an important technique which is used to study the dynamics of groundwater systems. Although, complex groundwater system with large set of parameters and associated uncertainty with those parameters makes modelling exercise difficult. In this study, development of groundwater model for Varanasi city and near around area was prompted to understand the groundwater dynamics and future groundwater resource scenarios in the region. The model was developed for the area of 2785 km2, where aquifer thickness varied up-to 150 m. The model grid consisted of 210 rows and 210 columns with each cell size of 250 m × 250 m. To realize the different type of underground formations, model was built for five layers with recharge entering the aquifer from surface infiltration through the overlying confining unit and from seepage through riverbeds. The maximum part of the model domain is surrounded by the Ganga River, which was taken as a hydrologic boundary for the model. Model simulations were made to quantify groundwater flow within the alluvial aquifer as well as flow into and out of the system. The groundwater model was developed for the transient state condition for the year of 2006 to 2017. Several criteria were used during model development and calibration to determine how fine the model simulated conditions in the aquifer. Model calibration was done on the values of hydraulic conductivity and recharge rates. A root-mean-square error analysis was performed during calibration to serve as a criterion to minimize differences between observed and model computed water levels. Further, calibrated model was used to analyze different scenarios to understand the future scenario of water resources. © 2020, Springer Nature B.V.